Depiction of a male figure on the Torana - Temples of India Project Team (Jio Institute, 2024)
The male figure on one of the pillars of the torana (ornamental gateway) depicts a standing male figure standing with folded hands near his chest. This figure is likely a deity as he wears a crown and heavy jewellery and has a mark on his chest commonly found on Jaina deities. His charming visage features raised eyebrows, a mustache, and a beard.